Procedure-Related Complication of Willis Covered Stent in the Treatment of Blood Blister-Like Aneurysm: Stent Detachment from Dilating Balloon - Zhang, Yuxiang; Zhang, Yupeng; Liang, Fei; Jiang, Chuhan (Frontiers in Neurology, 2017)
The use of Willis covered stent (WCS) for intracranial aneurysms has increased based on the promising results of previous studies about its safety and effectiveness. Simultaneously, with the accumulation of cases, reports about peri-procedural complications are emerging. In our department, 25 patients were treated WCS. We here report an unexpected procedure-related complication occurred in the treatment with the WCS for a blood blister like aneurysm (BBA). During the treatment, the distal end of the stent (portion) or the whole stent (whole) detached from the dilating balloon due to the access route tortousity and extracorporeal gas exhaust maneuver. A half-dilating technique followed to retrieve the detached stent. The procedure is detailed in this report and the possible reasons and approach are explored.